Structure and dynamics of cutinase encapsulated in isoreticular metal organic framework-74-VI - Tuan Kob @ Yaakub, Nurul Azura (2019)
Cutinase is a serine hydrolases enzyme that is widely used as a biocatalyst to produce industrially important chemicals ranging from pharmaceuticals to biological and food additives. However, low thermal stability and lack of efficient recovery are the limitation of cutinase. Enzyme immobilization is one of the techniques used to improve enzyme stability and activity. Recently, immobilization with porous materials such as metalorganic frameworks (MOFs) have shown to improve the thermostability of enzymes even in extreme conditions. Here, quantum mechanics (QM) calculations and molecular dynamics (MD) simulations were performed in order to investigate the structural stability of cutinase when encapsulated within an IRMOF-74-VI. Ab initio calculations were performed on the crystal structure of IRMOF-74-VI to obtain partial atomic charges for IRMOF-74-VI atoms. Then, MD simulations of cutinase and cutinase-IRMOF-74-VI in water were performed at different temperatures (300, 350, 400, 450 and 500 K) and 1 atm pressure. The encapsulated cutinase showed greater stability than the free enzyme. Although the average root mean square deviation (RMSD) value increased for both systems with temperature, the cutinase-IRMOF-74-VI exhibited lower RMSD values when compared to free-cutinase especially at 500 K. IRMOF-74-VI was able to control the strong fluctuations at higher temperatures and thereby, helped retain the cutinase structure. The key interactions that maintained the stability of cutinase were identified, such as hydrophobic interactions between amino acid residues of Pro193 and Thr45 with aromatic ring of IRMOF-74-VI. In addition, ion pair interactions between Arg96 residue and carboxylate group of IRMOF-74-VI was found to have a distance of 4.53 Å and was classified as a strong salt bridge. MD simulations also have been employed to study the effect of encapsulation towards stability and flexibility of cutinase in different solvents (water, ethanol and hexane) at room temperature. Cutinase-IRMOF-74-VI in water and ethanol produced lower RMSD values (0.14 ± 0.006 and 0.17 ± 0.017 nm respectively) compared to cutinase-IRMOF-74-VI in hexane (0.24 ± 0.015 nm). Further analysis also showed that cutinase-IRMOF74-VI complex was more stable in polar solvent. Cutinase- IRMOF-74-VI exhibited the highest number of intermolecular interactions with hexane compared to water and ethanol, leading to the least stable conformation between the three solvents. These findings demonstrate the potential for cutinase-encapsulation applications in cage-like pore frameworks by showing that encapsulation of cutinase with IRMOF-74- VI helps to retain the structural integrity at high temperature. However, IRMOF-74-VI destabilized cutinase in hexane compared to higher polarity solvents which are ethanol and water. This information can be used to optimize cutinase-MOF applications and develop new cutinase-specific MOF for biocatalysis and biosensing purposes. The interactions between cutinase and IRMOF-74-VI under different temperatures and solvents would be beneficial as guideline for future rational design of enzyme-MOF biocatalysts.